A NEW RECIPE FROM MY FACEBOOK: HOW DIGITAL LITERACY IMPACTING INNOVATION OF SMALL CULINARY ENTERPRISES IN INDONESIA - Aji, Angga Prawadika (Master of Communication Science Program, Universitas Diponegoro, 2023)
This paper is written based on a qualitative approach, to explore the ability to use communication technology by micro, small, and medium enterprises (MSMES) within the culinary field to support their ability to innovate in developing countries such as Indonesia. A total of 30 small and micro enterprises from the two biggest cities in East Java province participated in this empirical study. The data collection system is carried out using a semistructured interview that looks at the ability of business users to understand the internet as a media through four digital literacy elements, namely the ability to access, analyze, evaluate, and create messages. Based on the results of comparative analysis, it was found that the majority of MSMES owners have just reached the access phase, which is the initial phase where users are connected to the internet and utilize the most basic features of application services. MSMES owners only use internet technology for informal communication purposes and access to entertainment. One of the most important points from the results of the interview is the existence of religious issues which hamper the willingness of some MSMES owners to embrace the internet by creating reluctance and suspicion against the internet. One of them is the usury discourse that appears on non-cash payment technology and food purchasing services by online transportation.